The factors of selecting Malaysia as tourist destination - Alam, A. S. A. Ferdous; Er, A. C; Begum, Halima; Alam, Md Mahmudul (MCSER Publishing, Rome-Italy, 2015)
Tourism is an emerging economic sector for Malaysia.The purpose of this study is an attempt to understand the factors that attract tourists to visit Melaka State of Malaysia.The primary data were collected through questionnaire survey on 735 tourists who visited the state of Melaka, Malaysia.This study used descriptive statistics, confirmatory factor analysis, and structural equation modelling (SEM) in order to analyze and draw the inferences.Model fit was initially tested using the overall fit and regression paths. Then the hypothesized model was analysed and modified based on the results of the analysis to find a better fit of the data and to more adequately describe the relationships between the factors. The study found that several economic, environmental, cultural and community factors have positive significant influence in attracting tourists to Melaka.